Virtual Pathology Education in Medical Schools Worldwide during the COVID-19 Pandemic: Advantages, Challenges Faced, and Perspectives - Angela Ishak; Mousa M. AlRawashdeh; Maria Meletiou-Mavrotheris; Ilias P. Nikas (Diagnostics, 2022)
The COVID-19 pandemic shifted pathology education in medical schools worldwide towards online delivery. To achieve this goal, various innovative platforms were used by pathology educators and medical students, facilitating both synchronous and asynchronous learning. The aim of this study was to review the published evidence regarding remote pathology teaching at the medical school level during this period, present our own experience, and provide some perspectives regarding the best mode of pathology teaching post-pandemic. Among its advantages, virtual pathology education was considered among students and educators as convenient, flexible, and engaging, while learning outcomes were met and students’ academic performance was in general satisfactory. However, several challenges were faced. For instance, suboptimal internet connection compromised the flow of classes and was even associated with a lower academic performance. The lack of hands-on laboratory activities, such as operating the light microscope and tissue grossing, and the reduced student interactions among themselves and their instructors, were also pointed out as significant drawbacks of remote pathology education. Whereas online education has multiple advantages, experiencing the physical university environment, in-person interactions and teamwork, exposure to the “hidden curriculum”, and hands-on activities are vital for medical school education and future student development. In conclusion, the implementation of a blended approach in pathology education—where online and face-to-face sessions are jointly used to promote students’ engagement, interaction with their instructors and peers, and learning—could be the most optimal approach to pathology teaching in medical schools post-pandemic.